KEMISKINAN DI PROVINSI JAWA TENGAH 2018 - 2021, APA SAJA PENYEBABNYA? - Solikhin (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
One of the Central Java Provincial Government programs is to reduce the number of people living in poverty. The Central Java Provincial Government target in 2021 was to lower poverty rate to below ten percent. Therefore, it is necessary to determine factors affecting the poverty rate in Central Java. This study aimed to analyze the effect of the Human Development Index, total population, Gross Regional Domestic Product (GDRP), and the impact of the Covid-19 pandemic on the poverty rate in regencies/municipalities in Central Java. The study on the impact of the Covid-19 pandemic on the poverty rate in Central Java Province has never been carried out. This study was different from the previous studies. This study used panel data regression by using 2018-2021 data from Statistics Indonesia (BPS). In this study, the result of the best model selection was the random effect model. The result of this study indicated that Human Development Index (HDI) had a negative and significant effect, total population had a positive and insignificant, GRDP had a positive and significant effect, and the impact of Covid-19 pandemic had a positive and significant effect on the poverty rate.